2015
DOI: 10.1021/acsnano.5b02432
|View full text |Cite
|
Sign up to set email alerts
|

Realization of 13.6% Efficiency on 20 μm Thick Si/Organic Hybrid Heterojunction Solar Cells via Advanced Nanotexturing and Surface Recombination Suppression

Abstract: Hybrid silicon/polymer solar cells promise to be an economically feasible alternative energy solution for various applications if ultrathin flexible crystalline silicon (c-Si) substrates are used. However, utilization of ultrathin c-Si encounters problems in light harvesting and electronic losses at surfaces, which severely degrade the performance of solar cells. Here, we developed a metal-assisted chemical etching method to deliver front-side surface texturing of hierarchically bowl-like nanopores on 20 μm c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
110
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 28 publications
0
110
0
2
Order By: Relevance
“…Savin et al6 even demonstrated that Si nanopillars textured solar cell brings 3% higher in daily energy production as compared to the conventional Si micropyramids (SiMPs)‐textured solar cell, which benefits from its better angular acceptance. Hence, considerable efforts have been focused on integrating Si nanostructures into various solar cells, such as diffused homojunction cells,10, 11, 12 heterojunction cells,13, 14 photo‐electrochemical cells,15 hybrid cells,16, 17, 18 carrier‐selective contact cells,19 and ultrathin crystalline Si (c‐Si) cells 20…”
Section: Introductionmentioning
confidence: 99%
“…Savin et al6 even demonstrated that Si nanopillars textured solar cell brings 3% higher in daily energy production as compared to the conventional Si micropyramids (SiMPs)‐textured solar cell, which benefits from its better angular acceptance. Hence, considerable efforts have been focused on integrating Si nanostructures into various solar cells, such as diffused homojunction cells,10, 11, 12 heterojunction cells,13, 14 photo‐electrochemical cells,15 hybrid cells,16, 17, 18 carrier‐selective contact cells,19 and ultrathin crystalline Si (c‐Si) cells 20…”
Section: Introductionmentioning
confidence: 99%
“…The n -type-doped Si with a thickness of 300 μm and a resistivity of 1~5 Ω·cm (i.e., doping concentration, 1.0~4.7 × 10 15  cm –3 ) was used in our experiment, which is well matched with p -type PEDOT:PSS. Detailed experimental fabrication process can be found in our previous publications [6, 8, 13, 16]. A highly conductive PEDOT:PSS with thickness of ~103 nm was spin coated on the front surface of Si to work as an antireflection and hole-conductive layer [20], as well as to form a junction [21].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, a p -type polymer of poly(3,4-ethylenedioxy thiophene):polystyrenesulfonate (PEDOT:PSS) with a relatively high work function and a wide bandgap has been widely used in HHSCs as a hole-conductive material [47]. According to previous reports, power conversion efficiencies (PCEs) of over 13% have been achieved for PEDOT:PSS/Si HHSCs by a simple spin-coating method, demonstrating their great potentials in future photovoltaic application [816]. …”
Section: Introductionmentioning
confidence: 99%
“…[ 10,23 ] Our previous work demonstrated that the structure-reconstruction method could be acted on the as-fabricated high-aspect-ratio nanostructures to defi ne new nanostructures with decreased surface area, smooth surface, and enhanced light-trapping properties, which provided an alternative pathway to develop proper nanostructure arrays for high performance PEDOT:PSS/Si hybrid solar cells. [ 14,24 ] Herein, unique integrated nanocone-nanopillars (NC-NPs) dualstructured arrays have been successfully realized by combining colloidal lithography and a multiple metal-assisted chemical etching (MaCE) process. Furthermore, systematic investigations on optical properties of the obtained NC-NPs arrays were performed experimentally and numerically on the thin fi lm of c-Si substrates, in comparison with the single-form NPs arrays.…”
Section: Doi: 101002/aenm201501793mentioning
confidence: 99%
“…[ 12,13 ] The combination of organic electronics and matured silicon-based PV technology on ultrathin substrate has a huge potential for comparable effi ciency and signifi cant cost reduction compared to today's industrial Si solar cells. [ 14 ] However, effective light confi nement is essential for this kind of ultrathin PEDOT:PSS/Si hybrid cells due to the limited comparison purpose, the refl ection spectra corresponding to each stage on a 20 µm c-Si substrate are summarized in Figure 1 g. It should be noted that the height of all the nanostructures in this research was set as 1.5 µm, which presents the characteristic length-scale associated with c-Si to achieve a signifi cant photon absorption in the usable solar wavelength range. The rim region of the initial NPs shows porous structure due to the charge migration effect during the Au-assisted chemical etching process.…”
Section: Doi: 101002/aenm201501793mentioning
confidence: 99%